Teachers’ Experiences and Challenges in Implementing Listening Test in English Language Teaching at Afaada Islamic Boarding School - Sinta Tanwirul Hayah; Maslihatul Umami (Journal of English Language and Education, 2026)
This study explores teachers’ experiences and challenges in implementing listening tests within English Language Teaching (ELT) at Afaada Islamic Boarding School. Although listening assessment has received considerable attention in ELT research, limited studies have specifically examined teachers’ experiences in conducting listening tests in Islamic boarding school contexts, where educational facilities and students’ exposure to English may differ from those in mainstream schools. Using a qualitative descriptive approach, data were collected through in-depth interviews, classroom observations, and documentation involving three English teachers who were directly responsible for administering listening assessments. The findings reveal that teachers generally perceive listening tests as essential for assessing students’ comprehension and promoting active listening skills. However, they encounter several challenges, including limited technological resources, inconsistent audio quality, students’ low vocabulary mastery, and time constraints in preparing appropriate test materials. To address these challenges, teachers employ various strategies such as conducting pre-listening activities, simplifying instructions, and utilizing alternative audio sources to support students’ understanding. The study concludes that enhancing institutional facilities, providing professional development opportunities, and improving listening test design are crucial for promoting more effective listening assessment practices in Islamic boarding school settings.